1998
DOI: 10.1006/toxs.1998.2478
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Sublethal Exposure to the Protein Phosphatase Inhibitor Microcystin-LR Results in Multiple Dose-Dependent Hepatotoxic Effects

Abstract: The purpose of this study was to relate dose-dependent hepatotoxicity stemming from prolonged exposure to sublethal concentrations of the cyclic heptapeptide microcystin-LR (Mcyst) to hepatic Mcyst concentrations and protein phosphatase activity. Mcyst is a potent inhibitor of protein phosphatase types 1 and 2A (PP1 and PP2A). Twenty male Sprague-Dawley rats were infused continuously with 0, 3, 6, or 9 micrograms Mcyst/day for 28 days using intraperitoneal mini-osmotic pumps containing highly purified toxin or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 47 publications
5
36
0
3
Order By: Relevance
“…The presence of clear cytoplasmic vacuoles in pericentral areas was reported previously (40). In this study, oilred-O-stained sections demonstrated the presence of lipid within these vacuoles.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The presence of clear cytoplasmic vacuoles in pericentral areas was reported previously (40). In this study, oilred-O-stained sections demonstrated the presence of lipid within these vacuoles.…”
Section: Discussionsupporting
confidence: 88%
“…Histologic lesions in the liver of rats exposed to prolonged sublethal doses of MCLR were examined to determine whether they were consistent with those induced by oxidative damage, hepatic concentrations of the lipid peroxidation product, malondialdehyde, were correlated with dose of MCLR given, and liver slices from MCLRexposed rats were tested for susceptibility to the oxidizing agent tert-butyl hydroperoxide. gain was seen in a previous study (40) were treated with 1 mM tert-butyl hydroperoxide for 2 hr.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…analogous to those in mammals Li et al, 2005;Solter et al, 1998;Tencalla and Dietrich, 1997;Råbergh et al, 1991). Li et al (2005) reported that intrahepatic hemorrhage occurred in bighead carp (Aristichthys nobilis) injected intraperitoneally with crude MC extracts.…”
Section: Groupsmentioning
confidence: 81%
“…Problems related to toxigenic cyanobacteria seem to be of increasing importance due to their potential risk to animal and human health, and in a recent study by Chen et al (2009), microcystins were identified for the first time in the serum of a chronically exposed human population (fishermen at Lake Chaohu, China) together with indication of hepatocellular damage. Extracts of toxic cyanobacteria given orally, intraperitoneally, or intravenously in acutely and subacutely toxic doses may cause hepatotoxicity or even death of fish and mammals (Ernst et al, 2006;Falconer et al, 1988;LeClaire et al, 1995;Li et al, 2005;Lovell, 1989;Miura et al, 1989;Solter et al, 1998).…”
Section: Introductionmentioning
confidence: 99%